Intramembrane proteolysis at a glance: from signalling to protein degradation - Kühnle, Nathalie; Dederer, Verena; Lemberg, Marius (Journal of cell science, 2019)
Skip to Next Section - Over the last two decades, a group of unusual proteases, so-called intramembrane proteases, have become increasingly recognized for their unique ability to cleave peptide bonds within cellular membranes. They are found in all kingdoms of life and fulfil versatile functions ranging from protein maturation, to activation of signalling molecules, to protein degradation. In this Cell Science at a Glance article and the accompanying poster, we focus on intramembrane proteases in mammalian cells. By comparing intramembrane proteases in different cellular organelles, we set out to review their functions within the context of the roles of individual cellular compartments. Additionally, we exemplify their mode of action in relation to known substrates by distinguishing cleavage events that promote degradation of substrate from those that release active domains from the membrane bilayer.